Development of Biology E-Flashcard – Based Instructional Resource for Tenth – Grade Topic: Classification of Living Organism at SMA Negeri 2 Gorontalo – High School - Devliyanti Halusa; Masra Latjompoh; Regina Valentine Aydalina; Chairunnisah J. Lamangantjo; Ilyas H. Husain; Syam S. Kumaji (Universitas Labuhanbatu, 2025)
Background: Several students experience difficulties in mastering biological classification concepts. To address this issue, a digital E-Flashcard was developed as an instructional medium that supports technology-integrated learning, enhances motivation and comprehension, and offers flexible and practical use. This study evaluates the validity, practicality, and impact on learning outcomes of the E-Flashcard designed for Tenth-grade students at SMA Negeri 2 Gorontalo. Methodology: This study employed a Research and Development (R&D) method using the ADDIE development model, with a one-group pretest-posttest design involving 20 students from class X4 at SMA Negeri 2 Gorontalo. The instruments used included interview instruments, media and material validation instruments, and pretest and posttest instruments. Findings: The evaluation results indicated that the developed E-Flashcard met high feasibility standards, with material validation reaching 95.33% and media validation achieving 91%, both categorized as very feasible. Practicality assessment showed highly positive responses, reflected by a 98.5% score from teachers and 86% from students, both within the very practical category. Furthermore, analysis of learning improvement based on pretest and posttest scores yielded an N-gain value of 0.55, which falls into the moderate improvement level. These findings confirm that the E-Flashcard media satisfies the criteria of validity and practicality and demonstrates a meaningful improvement in student learning outcomes during limited-scale implementation. Contributions: This research advances digital biology instruction by introducing and empirically validating an ADDIE-based E-Flashcard model that enhances students’ conceptual understanding of biological classification, offering a scalable alternative to conventional printed flashcards in secondary education